Joint Optimization of Time and Aperture Resource Allocation Strategy for Multi-Target ISAR Imaging in Radar Sensor Network - Wang, Dan; Zhang, Qun; Luo, Ying; Liu, Xiaowen; Ni, Jiacheng; Su, Linghua (IEEE sensors journal, 2021)
Reasonable and effective resource allocation strategy can fully utilize the system potential of the radar sensor network especially under the limited resources. In this paper, a joint time and aperture resource allocation optimization problem of multi-target inverse synthetic aperture radar (ISAR) imaging in phased-array radar sensor network with game theory is investigated. The purpose of the resource allocation optimization problem is to complete the whole imaging tasks with high resolution within limited time and aperture resources. Obviously, the competition for radar resources exists among the targets under resource constraints. After analyzing the relationship between image resolution and time and aperture resources, the resource allocation optimization problem which is also a distributed decision problem is established and turns out to be an exact potential game. Thereafter the optimal resource allocation strategy is obtained by finding a Nash equilibrium (NE) strategy with an improved best response dynamic (IBSD) algorithm. Numerical experiments show the effectiveness of the proposed algorithm which can obtain a satisfied resource strategy profile.